Does the East Greenland Current exist in the northern Fram Strait? - M. E. Richter; M. E. Richter; W.-J. von Appen; C. Wekerle (Ocean Science, 2018)
Warm Atlantic Water (AW) flows around the Nordic Seas in a cyclonic boundary current loop. Some AW enters the Arctic Ocean where it is transformed to Arctic Atlantic Water (AAW) before exiting through the Fram Strait. There the AAW is joined by recirculating AW. Here we present the first summer synoptic study targeted at resolving this confluence in the Fram Strait which forms the East Greenland Current (EGC). Absolute geostrophic velocities and hydrography from observations in 2016, including four sections crossing the east Greenland shelf break, are compared to output from an eddy-resolving configuration of the sea ice–ocean model FESOM. Far offshore (120 km at 80.8° N) AW warmer than 2 °C is found in the northern Fram Strait. The Arctic Ocean outflow there is broad and barotropic, but gets narrower and more baroclinic toward the south as recirculating AW increases the cross-shelf-break density gradient. This barotropic to baroclinic transition appears to form the well-known EGC boundary current flowing along the shelf break farther south where it has been previously described. In this realization, between 80.2 and 76.5° N, the southward transport along the east Greenland shelf break increases from roughly 1 Sv to about 4 Sv and the proportion of AW to AAW also increases fourfold from 19±8 % to 80±3 %. Consequently, in the southern Fram Strait, AW can propagate into the Norske Trough on the east Greenland shelf and reach the large marine-terminating glaciers there. High instantaneous variability observed in both the synoptic data and the model output is attributed to eddies, the representation of which is crucial as they mediate the westward transport of AW in the recirculation and thus structure the confluence forming the EGC.